2020
DOI: 10.1039/d0ja00211a
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide analysis using collision–reaction cell ICP-MS technology: a review

Abstract: The analysis of radionuclides (RN) is of major concern in different fields like the environment, geosciences, the nuclear industry, and medical research. Inductively coupled plasma mass spectrometry (ICP-MS) is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 213 publications
0
16
0
Order By: Relevance
“…The inductively coupled plasma mass spectrometry (ICP-MS) has become the most powerful analytical tool for measuring Pu isotopes in environmental samples, due to its easier accessible with relatively lower cost to AMS and TIMS, faster analysis, higher sensitivity and lower detection limits to the traditional alpha spectrometry, as well as the ability to obtain isotopic information [14,15]. However, for ICP-MS detection of Pu isotopes, the peak tailing of 238 U + and uranium hydrides ( 238 U 1 H + and 238 U 1 H 2 + ) were the major spectral interferences limiting the accurate determination of 239 Pu and 240 Pu, especially for environmental samples with high U and low Pu concentrations [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inductively coupled plasma mass spectrometry (ICP-MS) has become the most powerful analytical tool for measuring Pu isotopes in environmental samples, due to its easier accessible with relatively lower cost to AMS and TIMS, faster analysis, higher sensitivity and lower detection limits to the traditional alpha spectrometry, as well as the ability to obtain isotopic information [14,15]. However, for ICP-MS detection of Pu isotopes, the peak tailing of 238 U + and uranium hydrides ( 238 U 1 H + and 238 U 1 H 2 + ) were the major spectral interferences limiting the accurate determination of 239 Pu and 240 Pu, especially for environmental samples with high U and low Pu concentrations [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above strategies, the collision-reaction cell (CRC) technology has widely been applied to ICP-MS (e.g., triple quadrupole ICP-MS) as a straightforward means [15,18] to eliminate uranium interferences for measurement of plutonium isotopes. The CRC with the application of different collision/reaction gases (e.g., NH 3 -He, CO 2 , O 2 ) has shown its ability to effectively remove uranium interferences by more than 15 times compared to the conventional ICP-MS [15,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conditions, signal due to 129 Xe + is greatly reduced 19,20,29 but not completely eliminated. Furthermore, although iodine oxidation by O 2 (eqn (4)) is not thermodynamically favourable (DHr ¼ 2.08 eV), 15 this chemical reaction takes place inside the collision/reaction cell (Fig. 6) and therefore directly affect the sensitivity of iodine.…”
Section: Measurement Mediummentioning
confidence: 99%
“…Several recent works have shown that ICP-MS (Inductively Coupled Plasma – Mass Spectrometry) and more specifically ICP-MS/MS is an excellent and affordable alternative to AMS for the measurement quantification of 129 I and the isotopic ratio 129 I/ 127 I (ref. 7, 14 and 15) with a limit of detection of ∼100 mBq L −1 and 10 −6 , respectively, without chemical treatment. This quantification is however a real challenge due to the extreme volatility of iodine which could decrease sensitivity and induce memory effects.…”
Section: Introductionmentioning
confidence: 99%